20th Cracow Methodological Conference: Philosophy in Science - Urbańczyk, Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2016)
The 20th Cracow Methodological Conference took place on May 30-31, 2016, at the Polish Academy of Arts and Sciences in Kraków. The meeting brought together physicists, cosmologists, mathematicians and philosophers interested in research program called philosophy in science started and popularized by Michał Heller. It is worth noting that the 20th Cracow Methodological Conference was dedicated to Professor Heller and can be considered as a contribution to the celebration of the 80th anniversary of his birthday.